Characterization of the logistical capacities in the strawberry producing agricultural associations in the municipalities of Soacha and Sibaté - Barrera Bello, Laura Nataly; Sandoval Cifuentes, Yuli Andrea; Gallego Pinzón, Erika Gisseth; Córdoba Berrio, Arturo Yesid; Castro Mateus, Carlos Eduardo (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2021)
Agricultural logistics in Colombia faces great challenges, due, among other factors, to the low investment in the sector, the high level of intermediation in the agri-food supply chain, which causes a decrease in the monetary amount received by producers and a high price paid by the final consumer, and to factors such as low associativity, added to the poor organization and lack of capacities or capabilities of the existing associations. Within these capacities is the technical assistance required by the associates and the means for the commercialization of their products. They are not having the necessary capacities, for this reason, losses are generated in producers, as they do not receive adequate remuneration for their crops. This discourages production and impairs the quality of life of farmers. Therefore, it is proposed to carry out an analysis to strengthen the logistics capacities and capabilities of strawberry producing associations, from two approaches. The first one refers to physical capacities, oriented to means such as transportation, facilities and technological means of information and traceability. The second one includes capabilities in the form of logistics modes, encompassing three fundamental processes: provisioning, storage and inventory, and distribution. For the analysis of this situation, strawberry producers belonging to agricultural associations in the municipalities of Soacha and Sibaté, the main producers of this fruit at the national level, are established as a study focus. The study methodology will be developed from a pragmatic approach, with the use of mixed strategies, through surveys and semi-structured interviews as instruments for collecting primary information.